Nature and man in Doris Lessing’s early small prose - Савина, Виктория Викторовна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The article deals with the consideration of Doris Lessing’s early small prose. The unique component of the works of this period becomes an original interpretation and a unique artistic solution of nature and a human being problems. Analysis of the concepts "nature" and "man" made it possible to reveal their dual character reflecting the author’s vision of the colonial world of Doris Lessing’s prose. Additionaly, the different perceptions of children and adults were examined in the writer’s early stories.